THE NATIONAL IDENTITY AND ITS ELEMENTS - Munkhbaatar Purevsuren,; Erdenechimeg Bor, (International Journal of Innovative Technologies in Social Science, 2025)
Throughout history, the united nation has consistently advanced the prosperity of their country, enhanced the well-being of their citizens, and reinforced the sovereignty of their nation. Democracy, freedom, and unity are principles that should be treasured by the populace. In the absence of unity, no amount of nationalism can be effective. Nations must safeguard their national identity, shield it from outside forces, and maintain national unity and social stability that is resilient to any threats. This article will explore the essence of national identity and the elements that foster national unity.